Blood Flow and Shear Stress Allow Monitoring of Progression and Prognosis of Tumor Diseases - Barral, Matthias; El-Sanharawi, Imane; Dohan, Anthony; Sebuhyan, Maxime; Guedon, Alexis; Delarue, Audrey; Boutigny, Alexandre; Mohamedi, Nassim; Magnan, Benjamin; Kemel, Salim; Ketfi, Chahinez; Kubis, Nathalie; et al. (Frontiers in Physiology, 2021)
In presence of a tumor angiogenesis, blood flow must increase leading to an elevation of blood flow velocities (BFVel) and wall shear stress (WSS) in upstream native arteries. An adaptive arterial remodeling is stimulated whose purpose consists in the enlargement of the arterial inner diameter aiming for normalization of BFVels and WSS. Remodeling engages delayed processes efficient only several weeks/months after initiation, independent from those governing expansion of the neo-vascular network. Therefore, during tumor expansion, there is a time-interval during which elevation of BFVels and WSS could reflect disease progression. Conversely, during period of stability, BFVels and WSS drop back to normal values thanks to remodeling processes achievement. Ovarian peritoneal carcinomatosis (OPC), pseudomyxoma peritonei (PMP) and superficial arteriovenous malformations (AVM) are diseases characterized by the development of abnormal vascular networks developed on native ones. In OPC and PMP, preoperative blood flow in the superior mesenteric artery (SMA) correlated with the per-operative peritoneal carcinomatosis index (OPC: n=21, R=0.79, p<0.0001, PMP: n=66, R=0.63, p<0.0001). Moreover, one year after surgery, WSS in the SMA allowed distinguishing PMP patients with, from those without disease progression (ROC-curve analysis, AUC=0.978 [0,902-0,999], p<0.0001, sensitivity: 100.0%, specificity: 93.5%, cut-off: 12.1 dynes/cm²). Similarly, WSS in the ipsilateral afferent arteries close to the lesion distinguished stable from progressive AVM (ROC-curve analysis, AUC: 0.988, [0.919-1.000], p<0.0001, sensitivity: 93.5%, specificity: 95.7%; cut-off: 26.5 dynes/cm²). Blood flow volume is indicative of the tumor burden in OPC, PMP, and WSS represents an early sensitive and specific vascular marker of disease progression in PMP and AVM.